2017
DOI: 10.1039/c7cp06489f
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles grown from methanesulfonic acid and methylamine: microscopic structures and formation mechanism

Abstract: Mechanisms of particle formation and growth in the atmosphere are of great interest due to their impacts on climate, health and visibility. However, the microscopic structures and related properties of the smallest nanoparticles are not known. In this paper we pursue computationally a microscopic description for the formation and growth of methanesulfonic acid (MSA) and methylamine (MA) particles under dry conditions. Energetic and dynamics simulations were used to assess the stabilities of proposed model stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 104 publications
(111 reference statements)
3
24
0
Order By: Relevance
“…Due to the substantial computational effort required, water is not included in the cluster structures or particle formation simulations of this study. It has been demonstrated that the enhancing effect of hydration is larger in the case of ammonia than dimethylamine (Olenius et al, 2017), and the reason is likely to be the number of available hydrogen bonds in the cluster structure (Yang et al, 2018). While the effect of water on guanidine-sulfuric-acid particle formation remains to be resolved, the possible enhancement can be expected to be small as the unhydrated clusters are already extremely stable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the substantial computational effort required, water is not included in the cluster structures or particle formation simulations of this study. It has been demonstrated that the enhancing effect of hydration is larger in the case of ammonia than dimethylamine (Olenius et al, 2017), and the reason is likely to be the number of available hydrogen bonds in the cluster structure (Yang et al, 2018). While the effect of water on guanidine-sulfuric-acid particle formation remains to be resolved, the possible enhancement can be expected to be small as the unhydrated clusters are already extremely stable.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the effect of hydration is larger for clusters containing ammonia than for those containing dimethylamine. This is due to structural effects, such as the number of available hydrogen bond donors and acceptors within the cluster (Yang et al, 2018). There are no measured particle formation data for guanidine; however, the good agreement between the simulations and experiments for dimethylamine and ammonia indicates that the simulations for guanidine can also be considered reliable.…”
Section: Ion-mediated Particle Formationmentioning
confidence: 99%
“…Particles of this size are much larger than the clusters shown in Figure , so that experimentally it is the combination of new particle formation and growth to this size that operationally defines particle formation in this system. In contrast, quantum chemical calculations suggest that water added to larger clusters formed from MSA‐MA resides on the surface or for increasing numbers of waters, inside the clusters …”
Section: New Particle Formation From the Reactions Of Methanesulfonicmentioning
confidence: 90%
“…Interestingly, if water vapor is introduced with the other reactants (as opposed to dry particles exposed to water vapor after formation), it significantly enhances new particle formation (Figure ) . Theoretical studies have been carried out to elucidate the reasons that water plays such an important role . As an example, Figure shows the calculated lowest energy structures of two small MSA‐TMA‐water clusters that are stable .…”
Section: New Particle Formation From the Reactions Of Methanesulfonicmentioning
confidence: 99%
“…Recently, NPF involving MSA and ammonia (A, NH 3 ), methylamine (M, CH 3 NH 2 ), or dimethylamine (D, CH 3 -NHCH 3 ) was investigated experimentally by the Finlayson-Pitts group using a special ow system. [19][20][21][22][23] Their results showed that MSA and A, M, or D easily form atmospheric aerosol particles under ambient conditions with medium or high humidity, where A, M, and D show different dependencies on the concentration of the MSA precursor. However, the micromechanism of formation of MSA-based clusters remains unresolved at the molecular level.…”
Section: Introductionmentioning
confidence: 99%